2009
DOI: 10.1002/ange.200902279
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Template Approach to High‐Nuclearity Silver(I) Alkynyl Clusters

Abstract: Erdnussförmig: Eine einfache Synthese großer Silbercluster nutzt Anionen als Template. Die Zahl an Silberatomen im Cluster lässt sich über die Größe des Templats und die Eigenschaften der Alkinylliganden einstellen. Für den größten Cluster mit 35 Silber(I)‐Zentren wurden Chromat‐Ionen als Templat eingesetzt (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…The cluster is nanosized with approximate dimensions of 3.0 2.0 nm. Two Mo 6 O 22 8À ions act as templates for the formation of the silver cluster, with the Ag À O bond lengths varying from 2.039(6) to 2.573 (5) , which are comparable to the values of 2.296(3)-2.581(2) found in [Ag 4 (dmso) 8 (Mo 8 O 26 )] n . [13] A total of 38 tBuCC ligands adopt m 3 or m 4 (with only two exceptional m 2 ) bridging modes to coordinate silver atoms peripherally and hold the cluster together.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…The cluster is nanosized with approximate dimensions of 3.0 2.0 nm. Two Mo 6 O 22 8À ions act as templates for the formation of the silver cluster, with the Ag À O bond lengths varying from 2.039(6) to 2.573 (5) , which are comparable to the values of 2.296(3)-2.581(2) found in [Ag 4 (dmso) 8 (Mo 8 O 26 )] n . [13] A total of 38 tBuCC ligands adopt m 3 or m 4 (with only two exceptional m 2 ) bridging modes to coordinate silver atoms peripherally and hold the cluster together.…”
supporting
confidence: 53%
“…Many inorganic polyatomic anions have been utilized in the construction of finite assemblies, and the size and shape of the directing anions dictate the geometry and connectivity of the final structures. [2][3][4] Recently, we developed a facile template approach for the synthesis of high-nuclearity silver(I) alkynyl clusters, [5] and a variety of silver clusters have been isolated with spherical chloride, triangular carbonate, and tetrahedral chromate templates. [5,6] Considering that polyoxometalates (POMs) are large oxo anions of group 6 or 5 elements and have good affinity to silver ions, [7][8][9][10] we attempted to incorporate POMs into silver alkynyl systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Single-crystal X-ray analysis [7] revealed that complex 1 is a solvated, neutral mirror-symmetric, cashewnut-shaped Ag 21 cluster encapsulating a pair of template chloride ions ( Figure 1), with argentophilic Ag···Ag bond distances in the range 2.811(2)-3.188 (2) . Each chloride coordinates to six silver atoms with Ag···Cl distances varying from 2.581(6) to 3.028 (6) , which are shorter than those found in [Ag 19 (C CtBu) 11 (CF 3 CO 2 ) 7 Cl] (2.940-3.847 ) and [Ag 14 (CCtBu) 12 Cl]BF 4 (3.116-3.297 ). [8] The cluster can be described as consisting of one [(tBuPO 3 )VO 2 (OH)] 2À and two [(tBuPO 3 ) 3 V 3 O 6 (OH)] 4À building units linked together through the Cl 2 @Ag 21 core.…”
mentioning
confidence: 98%
“…[4] The multinuclear RÀCC'Ag n (n = 3, 4, 5; R = alkyl, aryl, heteroaryl) metal-ligand supramolecular synthon [5] is a versatile building block for the anion-templated synthesis of high-nuclearity silver(I) ethynide clusters. [6] Recently, we reported a high-nuclearity mixed-metal anionic silver(I) ethynide cluster, [(V 2 O 7 ) 2 @Ag 44 (CCtBu) 14 @(V 32 O 96 )] 10À , which was synthesized by condensation and cyclic oligomerization of [VO 3 ] À units in an organic medium in which a globular (V 2 O 7 ) 2 @Ag 44 cluster serves as a cationic template to induce the assembly of a "cluster within a cluster", with its outer shell composed of a polyoxovanadium(V) macrocycle {V 32 O 96 }. [6h] We have now isolated three unprecedented mixed-metal giant clusters with the silver(I) tert-butylethynide moiety and various phosphonate-functionalized oxovanadate building blocks as their surface components, as well as different numbers and kinds of anionic species as their encapsulated templates: {Cl 2 @Ag 21 (C CtBu) 9 -[(tBuPO 3 ) 3 V 3 O 6 (OH)] 2 [(tBuPO 3 )VO 2 (OH)] (The reaction of (Et 4 N)VO 3 in methanol with tBuPO 3 H 2 , AgCCtBu, AgBF 4 and a small amount of (BzEt 3 N)Cl as a chloride source yielded {Cl 2 @Ag 21 (CCtBu) 9 [(tBuPO 3 ) 3 -V 3 O 6 (OH)] 2 [(tBuPO 3 )VO 2 (OH)](MeOH) 2 (H 2 O) 2 }·2 MeOH ·2 H 2 O (1).…”
mentioning
confidence: 99%